Application of shariah principles in Islamic foreign exchange options - Nor Fahimah, M.R.; Ahmad Sufian, C.A. (2016)
In accordance with the dire need for derivative-like products, Islamic financial institutions eventually initiated their efforts to design a product with suitable contracts. Option-like Islamic products began to be offered by Islamic financial institutions a few years ago. Today, the products have proven to gain wider recognition, and several contracts are being used to construct an option-like effect and outcome. This study aims to evaluate the compliance of Islamic foreign exchange options with shariah principles. This study involves the collection and analysis of primary and secondary data from various sources. It also undertakes content analysis of the rulings of jurisprudence scholars on several shariah principles. This study found that this Islamic FX option is still debatable on its permissibility from shariah perspective.